What it means for people to be mechanically ventilated via a tracheostomy at home: a qualitative study - Veronika Nelissen; Sabine Metzing; Wilfried Schnepp (University of Ostrava, 2019)
Aim: Some patients with an acute or chronic disease need home mechanical ventilation via a tracheostomy (invasive HMV). Little is known about the experiences of those affected. This study examined the experiences and life circumstances of people in Germany with invasive HMV. Design: A qualitative research design was selected. Methods: Problem-centered interviews were held with 20 patients who received invasive HMV. Grounded Theory method and methodology were used. Results: The affected people realize that they need invasive HMV and that this will allow them to continue to live. They want to be seen as human beings and to be able to trust the nursing staff. However, they need information and to be able to communicate, thereby regaining their independence and leading a self-determined life. Conclusion: The participants just want to live their life despite invasive HMV. The knowledge and experience of nurses can inspire trust and give those affected the necessary sense of safety.